Dynamics of Major Histocompatibility Complex Class II Compartments during B Cell Receptor–mediated Cell Activation - Danielle Lankar; Hélène Vincent-Schneider; Volker Briken; Takeaki Yokozeki; Graça Raposo; Christian Bonnerot (2002)
Antigen recognition by clonotypic B cell receptor (BcR) is the first step of B lymphocytes differentiation into plasmocytes. This B cell function is dependent on efficient major histocompatibility complex (MHC) class II–restricted presentation of BcR-bound antigens. In this work, we analyzed the subcellular mechanisms underlying antigen presentation after BcR engagement on B cells. In quiescent B cells, we found that MHC class II molecules mostly accumulated at the cell surface and in an intracellular pool of tubulovesicular structures, whereas H2-M molecules were mostly detected in distinct lysosomal compartments devoid of MHC class II. BcR stimulation induced the transient intracellular accumulation of MHC class II molecules in newly formed multivesicular bodies (MVBs), to which H2-M was recruited. The reversible downregulation of cathepsin S activity led to the transient accumulation of invariant chain–MHC class II complexes in MVBs. A few hours after BcR engagement, cathepsin S activity increased, the p10 invariant chain disappeared, and MHC class II–peptide complexes arrived at the plasma membrane. Thus, BcR engagement induced the transient formation of antigen-processing compartments, enabling antigen-specific B cells to become effective antigen-presenting cells.